Seeing 'tis Known in Contraries - Ratcliffe, Elizabeth Holly (My University, 1982)
The combination of empirical rigour and intuitive, aesthetic insight in Sapir's thought has been amply documented (cf Lowie 1965), but an assessment of the compatibility of the two, infused as they are in his theoretical formulations, has been lacking. Metaphorically, Sapir's approach may be said to oscillate between two types of vision: the empirical caution to see what is given to the senses, and an intuitive sense of implication--"the chronic inability to see just what is there". The present examination shows, in a more systematic fashion, how in various dimensions, Sapir's underlying epistemology evinces central inconsistencies reflective of this oscillation.
The findings should be important for current anthropologists following on Sapir's ideas. It is also suggested that at a more general level, research of this type is necessary for informed, self-critical development in anthropological theory.
Keywords: Anthropology; Anthropology